Instructed extinction in human fear conditioning: History, recent developments, and future directions. (27th July 2016) - Luck, Camilla C.; Lipp, Ottmar V.
Abstract : Instructed extinction is an experimental manipulation that involves informing participants after the acquisition of fear learning that the unconditional stimulus (US) will no longer be presented. It has been used as a laboratory analogue to assess the capacity of cognitive interventions to reduce experimentally induced fear. In this review, we examine and integrate research on instructed extinction and discuss its implications for clinical practice. Overall, the results suggest that instructed extinction reduces conditional fear responding and facilitates extinction learning, except when conditional stimulus valence is assessed as an index of fear or when fear is conditioned to images of animal fear‐relevant stimuli (snakes and spiders) or with a very intense US. These exceptions highlight potential boundary conditions for the reliance on cognitive interventions when treating fear in clinical settings.